2016
DOI: 10.3906/sag-1503-100
|View full text |Cite
|
Sign up to set email alerts
|

Levels of nitric oxide, asymmetric dimethyl arginine, symmetric dimethyl arginine,and L-arginine in patients with obsessive-compulsive disorder

Abstract: We found a significant decrease in ADMA, SDMA, and L-arginine as NO inhibitors between the groups, possibly because of an increase in NO. However, the insignificant increase in NO suggests that ADMA, SDMA, and L-arginine play direct and potentially important roles in OCD biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…From full‐text review of the resulting 31 papers, 14 did not meet inclusion criteria and 17 were included in our qualitative synthesis. Four of these were ineligible for quantitative synthesis, resulting in 13 studies considered for quantitative analysis . Two of these studies assessed the same sample, but data from both were included since they provided complementary information (i.e., distinct markers and correlation between TBARS and Y‐BOCS) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From full‐text review of the resulting 31 papers, 14 did not meet inclusion criteria and 17 were included in our qualitative synthesis. Four of these were ineligible for quantitative synthesis, resulting in 13 studies considered for quantitative analysis . Two of these studies assessed the same sample, but data from both were included since they provided complementary information (i.e., distinct markers and correlation between TBARS and Y‐BOCS) .…”
Section: Resultsmentioning
confidence: 99%
“…Growing evidence supports the possibility that psychiatric disorders may be considered multisystem disorders, with patients presenting altered immune and oxidative markers, when compared to healthy controls . Specifically for OCD, while its exact etiology and pathophysiology remain unknown, systemic dysregulation of inflammation and oxidative stress has been increasingly reported . Regarding inflammation, recent meta‐analyses have confirmed that patients with OCD have reduced plasma IL‐1β and increased anti‐basal ganglia antibodies, in comparison with healthy controls .…”
Section: Introductionmentioning
confidence: 99%
“…In other words, patients who showed improvements of OCD symptoms had lower values of NO and peroxynitrite in their sera. In other studies comparing the NO levels of patients with OCD with healthy controls, elevated levels were seen in patients as well [13]. …”
Section: Discussionmentioning
confidence: 99%
“…2 ), a stable marker of NO, that were positively correlated with YBOCS scores (Atmaca et al, 2005). Similarly, Yilmaz et al (2016) investigated variations in the levels of NO, asymmetric dimethyl arginine, symmetric dimethyl arginine, and L-arginine levels in patients with OCD. The investigators found that although NO levels were increased, albeit narrowly missing statistical significance, patients with OCD had significantly lower levels of asymmetric dimethyl arginine, symmetric dimethyl arginine, and L-arginine compared with the controls (Yilmaz et al, 2016).…”
Section: B Probing the Role Of Other Endogenous Processes In Obsessive-compulsive Disordermentioning
confidence: 99%